2014
DOI: 10.1186/1472-6963-14-354
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to applying a national quality registry for quality improvement in stroke care

Abstract: BackgroundNational quality registries (NQRs) purportedly facilitate quality improvement, while neither the extent nor the mechanisms of such a relationship are fully known. The aim of this case study is to describe the experiences of local stakeholders to determine those elements that facilitate and hinder clinical quality improvement in relation to participation in a well-known and established NQR on stroke in Sweden.MethodsA strategic sample was drawn of 8 hospitals in 4 county councils, representing a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 30 publications
0
49
0
1
Order By: Relevance
“…In line with this, a previous study has suggested that the presence of a purposeful and active management system supports planning, performing, and follow-up and thus contributes to continuous quality improvements. 43 Thus, future studies should attend to and explore how the leadership model fits with present management systems, or identify and attend to needs for adjustments. The insufficient routines for evaluation and feedback to staff members about their clinical performance in some of the participating units could have contributed to the discrepancy in views between managers and staff members regarding guideline recommendations and actual clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, a previous study has suggested that the presence of a purposeful and active management system supports planning, performing, and follow-up and thus contributes to continuous quality improvements. 43 Thus, future studies should attend to and explore how the leadership model fits with present management systems, or identify and attend to needs for adjustments. The insufficient routines for evaluation and feedback to staff members about their clinical performance in some of the participating units could have contributed to the discrepancy in views between managers and staff members regarding guideline recommendations and actual clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The growing literature indicates that clinical quality registries can provide vital information that can be used to facilitate improvements in practice16 with positive effects primarily on the processes of care, whereas measures on outcome of care are less often positively affected 16. Findings, however, are heterogeneous, indicating that neither a registry itself nor the reporting of data initiates change as quality improvement requires comprehensive approaches,17 including successful implementation of the registry and continuous data quality assurance, as well as transparency and timely feedback 18. Based on experiences from the field of stroke care, embracing a comprehensive quality assurance approach, including a culture with focus on quality, thorough data entry, and availability of feedback as well as willingness to act on feedback, is critical in order to achieve improved quality of care 18.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that staff members engaged in Riksstroke at the stroke unit level are aware of the need to identify unique selling points to involve their colleagues. 13 However, more collaborative efforts and an understanding of quality improvement are necessary if the data are to help improve stroke care and not just provide feedback. Managers are often considered key to support clinical quality improvement, 13 14 31 which our findings also support.…”
Section: Discussionmentioning
confidence: 99%
“…We identified sets of dependent and independent variables (indexes) by processing theoretical knowledge and clinical experience, including our previous qualitative studies, 13 …”
Section: Independent and Dependent Variablesmentioning
confidence: 99%
See 1 more Smart Citation